Research of Teaching in Counselor Education: A Collective Effort of Improved Rigor - Elizabeth A Prosek (Teaching and Supervision in Counseling, 2020)
This special issue in Teaching and Supervision in Counseling offers several perspectives of teaching, pedagogy, and learning theory in counselor education. In this article, the author conceptualizes signature pedagogies: surface, deep, and implicit structures in terms of research questions. Methodological design considerations are discussed to broaden the scope and rigor of research on teaching in counseling. Finally, strategies for improving a favorable review of research manuscripts for publication are provided.
Keywords: pedagogy; counseling; research; teaching; learning theory